Evaluated The Efficacy and Economic Viability of Movento® Insecticide Mustard Aphids Infesting Brassica napus - Khan , Fawad; Najiya Al-Arifa; Saffora Riaz; Madieha Ambreen; Kamran Khan; Uddin, Bahar; Hayat, Sidra; Tayab, Muhammad; Khan, Imtiaz Ali (Universitas Andalas, 2025)
This study evaluated the efficacy and economic viability of four concentrations of Movento® SC insecticide-Movento® 30 SC, Movento® 60 SC, Movento® 120 SC, and Movento® 240 SC-against mustard aphids infesting Brassica napus at the Agriculture Research Institute Tarnab farm during the 2021-2022 growing season. The study was conducted during the growing season of 2021-2022, with different concentrations of Movento® SC applied to control mustard aphids on Brassica napus. The research used a factorial randomized complete block design (RCBD) with two factors. Results indicated that diet type and population density significantly influenced the biological parameters of S. c. ricini. Silkworms fed castor leaves exhibited higher survival rates and heavier cocoon weights than those fed cassava leaves. Results revealed that Movento® 60 SC was the most effective in managing mustard aphids, resulting in the lowest aphid infestation level and the highest crop yield of 8526.7 kg/ha. This treatment also provided the highest net benefit of Rs.161,315.10/ha, with a cost-benefit ratio (CBR) of 18.50. While Movento® 120 SC and Movento® 240 SC were also effective in controlling aphids, they were less cost-effective than Movento® 60 SC. Movento® 30 SC showed the highest aphid infestation and the lowest economic returns. Movento® 60 SC provided the best combination of efficacy and economic benefit in managing mustard aphids in Brassica crops. It resulted in the maximum yield and net benefit, making it the most economically viable option. Although Movento® 120 SC and Movento® 240 SC were effective, they proved to be less cost-effective when compared to Movento® 60 SC. This suggests reassessing pest management strategies to balance optimal pest control with greater economic returns in mustard cultivation.